Óbitos por traumas e a doação de órgãos e tecidos para transplantes - Freitas, Rosane Almeida de (2014)
The external causes are considered a problem of the epidemic character and configure one of the most serious problems of Public Health in the world. In Brazil, the deaths by external causes present themselves as the second cause of death with increasing tendencies. This paper had as objective to characterize the victims of traumas and verify the denouement of the deaths occurred in relation to the effectuation or not of the organ donation and its causes. It is about a retrospective, transversal and descriptive study with secondary data. Were analyzed deaths of victims of external causes arising from trauma attended at the hospitals of the city of Maringá and its metropolitan region, in the year of 2012 with age between 2 and 70 years. Were excluded from the research deaths in the local of the accident, those of external causes not arising from trauma, as well as those ones that didn't have identification, for not characterizing themselves as potential organ donors. The data were collected through Reports of monthly deaths of the hospitals that have intra-hospital commission of Organs and Tissues Donation - CIHDOTT active sent to the Organization Commission of Organs Search - COPOTT in the 15th Health Regional of Maringá. The missing data were completed with the patients' records. Posteriorly the data were typed in the software Excel 2010 codified and analyzed in the program EPI info 7.1.3.0. To this analysis were used the descriptive statistics and charts of contingency, to which, whenever possible, was performed the chi-square test, and when the same was not suitable, it was utilized the exact test of Fisher. It occurred 1864 deaths, being 871 in the analyzed institutions within the age for donation, of these 15, 8% (134/871) potential donors, victims of trauma. 71, 6% (96/134) of the victims had encephalic Traumatism, of these 32, 3% (31/96) were submitted to the protocol of encephalic death and 4, 2% (4/96) initiated the protocol, however had cardio respiratory arrest (CRA) before the ending, 63,5% (61/96) had CRA. The prevalence was to the masculine sex 80, 6% (108/134) and predominant age of 18 to 40 years with 52, 23% (70/134). The traumas that occurred with higher frequency were the traffic accidents 56, 5% (76/134), among these 58% (44/76) were motorcyclists and the aggressions 25% (33/134) with 55% (18/33) by firearms. Among the relatives approached, only 51, 78% (29/56) authorized the donations. Among the motives of refusal 23% justified by religious convictions. From the cases of not donation of the approached patients, there was a higher negative in patients with encephalic death 61, 53% (16/26). The index of not approach was of 58, 20% (78/134), whereas the motives that had highlight were the cases of contra-indication by sepsis 39, 70% (31/78) and hemodilution 35,90 (28/78). Against the results, it is verified the necessity of implanting a continuous training to the health professionals, in what refers to the donation-transplant process, as the utilization of the protocols to the appropriate maintenance of the organs, early notification and better hemodynamic maintenance of the potential donors, once there was a high index of relatives not approached by motives many times reversible.